Confronting the Learning Crisis : Lessons from World Bank Support for Basic Education, 2012–22 (Approach Paper) - Independent Evaluation Group (Washington, DC : World Bank, 2022)
The achievement of learning outcomes has been a long-standing challenge for education systems across the developing world and has significant consequences for economic development. To realize the development aims of education investments, students need to learn, but too many have not, especially in low-income countries. The World Bank has sought to address this learning crisis for more than a decade through the pursuit of quality education that enhances learning outcomes. The Independent Evaluation Group’s (IEG) proposed evaluation will assess the extent to which the World Bank’s Education Global Practice (GP) and its predecessor, the Education sector unit, have supported efforts to improve learning outcomes over the past decade (fiscal years [FY]12–22). Based on that experience, the evaluation will assess the effectiveness, relevance, and adequacy of World Bank support to address the learning crisis. It will identify lessons and recommendations to inform the next education sector strategy and further development of the World Bank’s approach to this persistent development challenge and the exacerbation of learning deficits during the coronavirus (COVID-19) pandemic.